2012
DOI: 10.1371/journal.pone.0048068
|View full text |Cite
|
Sign up to set email alerts
|

Assessing European Egg Parasitoids as a Mean of Controlling the Invasive South American Tomato Pinworm Tuta absoluta

Abstract: The South American tomato pinworm (Tuta absoluta) has recently invaded Europe and is rapidly spreading in the Afro-Eurasian continent where it is becoming a major pest on tomato crops. Laboratory tests were undertaken to evaluate the potential of 29 European strains of Trichogramma parasitoids to control T. absoluta. In addition to the host itself, the host plant (tomato) was used during the laboratory tests in order to increase the chance of selecting the best parasitoid strains. Trichogramma females were pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
61
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 43 publications
(49 reference statements)
5
61
0
2
Order By: Relevance
“…Results showed that both T. richogramma species accepted T. absoluta eggs as host and the species of T. embryophagum exhibited promising (31.18%) parasitism when treated in combination with Bt vs. 23.05% of parasitism without Bt. Our result were in line with results obtained by Chailleux et al [23] that investigated twenty-nine Trichogramma speciesstrains on T. absoluta eggs under laboratory conditions and recorded the highest rate of egg parasitism (35.4%) for T. achaeae. Furthermore, we found a significant increase in the number of parasitized eggs when the tomato plants were simultaneously treated with Bt.…”
Section: Discussionsupporting
confidence: 93%
“…Results showed that both T. richogramma species accepted T. absoluta eggs as host and the species of T. embryophagum exhibited promising (31.18%) parasitism when treated in combination with Bt vs. 23.05% of parasitism without Bt. Our result were in line with results obtained by Chailleux et al [23] that investigated twenty-nine Trichogramma speciesstrains on T. absoluta eggs under laboratory conditions and recorded the highest rate of egg parasitism (35.4%) for T. achaeae. Furthermore, we found a significant increase in the number of parasitized eggs when the tomato plants were simultaneously treated with Bt.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, these insecticides also negatively impact the natural enemy populations of T. absoluta (Arnó and Gabarra 2011;Biondi et al 2013;Abbes et al 2015) owing to multiple potential side effects as described by Desneux et al (2007) in a review. The effectiveness of biological control using entomopathogenic organisms (González-Cabrera et al 2011;Ben Khedher et al 2015) beneficial insects (Ferracini et al 2012;Chailleux et al 2012;Chailleux et al 2013;Öztemiz 2013;Salehi et al 2016) present valuable alternative methods to synthetic pesticides. For example, the use of certain Miridae as Macrolophus pygmaeus Rambur or Dicyphus maroccanus Wagner appears to be a reliable biological alternative for the control of T. absoluta (Urbaneja et al 2013;Abbas et al 2014;Jaworski et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Adults emerged from parasitized T. absoluta eggs (4.8%, 97.5% and 90.0% adult emergence respectively), however, they appeared to be weak, smaller and with reduced longevity. Chailleux et al 16 also observed that adult trichogrammatids emerging from Tuta eggs possessed inferior biological traits like wing deformations, lower parasitism rates and reduced longevity. Some reports indicate that field releases of trichogrammatids were not consistently effective, which could have been because of the weak adults emerging from the parasitized T. absoluta eggs.…”
mentioning
confidence: 99%
“…However, information is scarce on the per cent Trichogramma adult emergence from parasitized Tuta eggs, and the parasitizing efficiency of the emerged adults. Laboratory, cage and greenhouse studies indicate that strainal variations exist in trichogrammatids with respect to their parasitizing efficiency on T. absoluta eggs [16][17][18][19] . In order to develop a Tuta adapted strain of Trichogramma, trichogrammatids which emerged from Tuta eggs were further allowed to parasitise rice moth (Corcyra cephalonica Stainton) eggs.…”
mentioning
confidence: 99%
See 1 more Smart Citation